The Formation of a Stable Political Governance: Structural-Functional and Morphological Analysis - A. D. Tumanov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2021)
The purpose of the article is to implement a systematic analysis of the factors of the formation of a stable system of political governance. To clarify the functions and structure of a stable political system, the characteristics of stability are highlighted, according to which the political system: has signs of legitimacy; is able to cope with the threat of illegitimate violence; supports the constitu-tional system; reproduces a model of behavior based on stability. Methodologically, the article is based on the works of classical and modern scientists (P. M. Khomyakov, M.A. Gaydes, I.B . Rodionov, A. A. Khomiakov). Makarycheva), devoted to the systematic analysis of political systems. The paper also uses morphological analysis, analysis of political eﬃciency, and in the ﬁnal part — the method of state-management design. The author comes to the conclusion that the functions and structure of the modern political system should be considered from the point of view of the deﬁni-tions of “political stability”, viewed through the prism of the absence of political threats, adaptive irremovability of political subjects and the balance of political forces. Political stability implies that the distribution of resources in society involves not only the institutional subsystem of the political system, but also the functional, regulatory and ideological subsystems. Morphological analysis demonstrates that a stable political system is characterized by a balanced interaction of subsystems, in which at least the institutional, regulatory and functional subsystems jointly determine the process of functioning and development of the political system. Stability is the basis and guarantee of po-litical development in the modern world, and stability is not contrary to innovative development or development in general. Both stability and development are the basic conditions for the development of a modern political system, methods of avoiding negative adaptation in the global environment. Stability is not synonymous with closeness — on the contrary, it implies horizontal and vertical mobility, a constitutional system, and a focus on maintaining the activity of political actors. At the same time, all these processes cannot be allowed to take their course and develop outside the political control of the vertical structures of power. Integrity as a system-wide property is an integral basis for the stability of the political system.